The kidnapping and murder of Little Skeegie Cash : J. Edgar Hoover and Florida's Lindbergh case - Waters, Robert A., 1944- (The University of Alabama Press, 2014)
Informed by thousands of pages of newly released FBI files, The Kidnapping and Murder of Little Skeegie Cash tells the gripping story of the only crime investigated by J. Edgar Hoover himself, the sensational 1938 murder of a five-year-old boy from the Florida Everglades. In his long and storied career, J. Edgar Hoover investigated only one case personally, the 1938 kidnapping and murder of five-year-old Floridian James "Skeegie" Cash. What prompted the director himself to fly from Washington, DC, to a rain-drenched hamlet on the edge of the Everglades? Congress had slashed